2016
DOI: 10.1186/s12942-016-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Geography and social distribution of malaria in Indonesian Papua: a cross-sectional study

Abstract: BackgroundDespite being one of the world’s most affected regions, only little is known about the social and spatial distributions of malaria in Indonesian Papua. Existing studies tend to be descriptive in nature; their inferences are prone to confounding and selection biases. At the same time, there remains limited malaria-cartographic activity in the region. Analysing a subset (N = 22,643) of the National Basic Health Research 2007 dataset (N = 987,205), this paper aims to quantify the district-specific risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 71 publications
5
33
2
1
Order By: Relevance
“…A gradient of malaria prevalence from rural (58.9%) to urban areas (33.9%) has been known in the Bata district of Equatorial Guinea (EG) [ 24 ]. This situation is consistent with the identified high-risk in the rural context that was found in West Papua, Papua [ 23 ] and East Nusa Tenggara [ 6 , 25 ]. A similar variation of spatial malaria distribution was observed in a cross-sectional study in rural areas in Haiti (4–41%), and demographic data indicated some focal disease transmission [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A gradient of malaria prevalence from rural (58.9%) to urban areas (33.9%) has been known in the Bata district of Equatorial Guinea (EG) [ 24 ]. This situation is consistent with the identified high-risk in the rural context that was found in West Papua, Papua [ 23 ] and East Nusa Tenggara [ 6 , 25 ]. A similar variation of spatial malaria distribution was observed in a cross-sectional study in rural areas in Haiti (4–41%), and demographic data indicated some focal disease transmission [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Spatial variation in malaria prevalence has to be taken into account in Indonesia [ 23 ]. The highest malaria prevalence was found in South Sorong, a known malaria endemic province [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, Anopheline species diversity and density decline from the lowlands to highlands [ 40 ]. Accordingly, poor villagers living in forested lowland areas in Papua, Indonesia, were found to be at higher risk of malaria infection than those in the highlands [ 41 ]. In contrast, a positive correlation between altitude and the abundance of Anopheles mosquitoes has observed in the highlands of Ethiopia, Colombia and Ecuador, particularly in warmer years [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This high prevalence of cases and mortality rates make malaria an infectious disease that should be watched out globally so that every country has a commission to eliminate this infectious disease. 3 Vector control is an essential component in preventing malaria. Such control is successful in reducing or disrupting malaria transmission when coverage is high.…”
Section: Introductionmentioning
confidence: 99%